(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
The study examined Digital technology integration and students’ academic performance in secondary schools in Abi LGA, Cross River State, Nigeria. One research questions and one null hypotheses were formulated to guide the study. Ex-post facto research design was adopted for the study. The population of the study comprised 232 teachers. Total samples of two hundred (200) respondents’ were randomly selected for the study. The selection was done through the simple sampling technique. The instrument used for the collection of data was the research questionnaire titled:" Digital technology integration and students’ academic performance (DTISAPQ)" validated by experts in Educational Management and test and measurement department. To test the hypotheses, Pearson product moment correlation statistical analysis was used. All the hypotheses were subjected to testing at .05 level of significant with critical values arid 198 degree of freedom. The study concludes that digital technology integration relate with students’ academic performance in secondary schools in Cross River State. It was recommended that ICT facilities should be provided to integrate students’ into technological advancement.